Yield and quality of carrots when using the Gumiton organo-mineral complex in conditions of radioactive contamination - et. al., Ratnikov A. N., (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this work is to assess the impact of Gumiton peat-based organo-mineral complex on the productivity and quality of carrots and the transition of 137Cs from soil to root crops under conditions of radioactive contamination. According to the results of field experiments on gray forest and soddy-podzolic soils of the Kaluga region of Russia, it is shown that leaf treatment with Gumiton of carrot plantings in different phases of crop development increases the yield of root crops by 20-40%, depending on the variety, soil type and agricultural background. Analysis of studies in the growing experiment on soddy-podzolic soil showed that Gumiton treatment increases the yield of carrots by 30%. The rate of decrease of 137Cs content is 1,2-1,25 times. Gumiton is a highly effective preparation for carrots, which increases the productivity and quality of the crop and helps to reduce the intake of 137Cs in root crops in radioactively contaminated areas.